Higher Levels of Urinary Thiocyanate, a Biomarker of Cruciferous Vegetable Intake, Were Associated With Lower Risks of Cardiovascular Disease and All-Cause Mortality Among Non-smoking Subjects - Wang, Qiang; King, Lei; Wang, Pei; Jiang, Guanhua; Huang, Yue; Dun, Changchang; Yin, Jiawei; Shan, Zhilei; Xu, Jian; Liu, Liegang (Frontiers in Nutrition, 2022)
Background: Epidemiologic studies on cruciferous vegetable (CV) intake and cardiovascular disease (CVD) were inconclusive. Objective: To investigate the associations of urinary thiocyanate, a biomarker of cruciferous vegetable intake, with cardiovascular disease (CVD) and all-cause mortality among non-smoking adults. Methods: This prospective cohort study comprised 10,489 non-smoking adults (weighted mean age, 46.8 years; 43.4% male) from the National Health and Nutrition Examination Survey 2001-2014. Non-smokers were defined as subjects with serum cotinine < 3 ng/mL. Urinary thiocyanate was measured with ion chromatography tandem mass spectrometry at baseline, and CVD and all-cause mortality were identified through linkage to National Death Index until December 31, 2015. Cox proportional hazards model was applied to estimate the hazard ratios (HRs) with 95% confidence intervals (CIs) for CVD and all-cause mortality. Results: A total of 800 deaths, of which 136 died of CVD, were ascertained within a median 7.8 years of follow-up. Urinary thiocyanate was positively correlated with total cruciferous vegetable intake among non-smoking adults (rs = 0.088, P < 0.001). Comparing extreme quartiles, the multivariate-adjusted HRs for CVD and all-cause mortality were 0.50 (95% CI: 0.29-0.85) and 0.75 (95% CI: 0.60-0.92), respectively. Each 1 μg/g creatinine increment of log-transformed urinary thiocyanate was associated with a 25% (HR: 0.75; 95% CI: 0.62-0.91) reduced CVD mortality risk and 12% (HR: 0.88; 95% CI: 0.81-0.96) reduced all-cause mortality risk. The documented inverse associations persisted in sensitivity analyses. Conclusions: Increased levels of urinary thiocyanate, a candidate biomarker of cruciferous vegetable intake, were associated with low risks of CVD and total mortality among non-smoking adults. This prospective biomarker-based study provided further evidence to support the cardiovascular benefits of cruciferous vegetables.